2016
DOI: 10.1002/srin.201600267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prior Microstructure and Heating Rate on the Austenitization Kinetics of 39NiCrMo3 Steel

Abstract: The formation of austenite from three different prior microstructures is studied in a 39NiCrMo3 steel, which, indeed, is widely used in the industry, especially for induction heating treatments, due to its resistance to thermal cracking. The starting microstructure of sorbite with fine carbides, sorbite with coarse carbides and stress-relieved martensite is examined in detail by optical microscopy, scanning electron microscopy, and Vickers microhardness measurements. Dilatometric tests are performed employing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…The preparation of the thin foils was realized by mechanical grinding until thickness of 70 µm, followed by mechanical punching to obtain 3 mm diameter specimens. The final polishing and etching were performed electrochemically using a twin-jet polisher STRUERS TENUPOL-3 (Struers S.A.S., Milan, Italy), with 95% acetic acid (CH 3 COOH) and 5% perchloric acid (HClO 4 ) solution, at 45 V and room temperature [26,27].…”
Section: Microstructural Studymentioning
confidence: 99%
“…The preparation of the thin foils was realized by mechanical grinding until thickness of 70 µm, followed by mechanical punching to obtain 3 mm diameter specimens. The final polishing and etching were performed electrochemically using a twin-jet polisher STRUERS TENUPOL-3 (Struers S.A.S., Milan, Italy), with 95% acetic acid (CH 3 COOH) and 5% perchloric acid (HClO 4 ) solution, at 45 V and room temperature [26,27].…”
Section: Microstructural Studymentioning
confidence: 99%
“…Most of cementite will directly nucleate at the existing undissolved cementite during the divorced eutectoid transformation, which will form spherical cementite. At last, during the subsequent holding, cementite will coarsen again, which is driven by the decrease of interfacial energy …”
Section: Resultsmentioning
confidence: 99%
“…[ 42,43 ] It was reported that for the conventional low‐alloy steel, the martensite‐to‐austenite transformation was a diffusive transformation at a lower heating rate, whereas it changed into a displacive transformation at the heating rate larger than 400 °C s −1 . [ 44 ] Settimi et al [ 45 ] also reported that the martensite‐to‐austenite transformation changed into displacive transformation at a large heating rate. Considering the far larger heating rate during laser surface hardening, the martensite‐to‐austenite transformation should also be a displacive phase transformation for 52100 steel.…”
Section: Discussionmentioning
confidence: 99%